The Impact of Mass Layoffs on the Educational Investments of Working College Students - Ben Ost; Weixiang Pan; Douglas A. Webber (Institute for the Study of Labor (IZA), 2016)
Analyzing how working students weather personal economic shocks is increasingly important as the fraction of college students working substantial hours has increased dramatically over the past few decades. Using administrative data on Ohio college students linked to matched firm-worker data on earnings, we examine how layoff affects the educational outcomes of working college students. Theoretically, layoff decreases the opportunity cost of college enrollment, but it could also make financing one's education more difficult, so the net effect is ambiguous. We find that layoff leads to a considerable reduction in the probability of employment while in school, but it has little impact on enrollment decisions at the extensive margin. On the intensive margin, we find that layoff leads to an increase in enrolled credits, consistent with the fact that the opportunity cost of college has decreased.
Keywords: I21; I23; J63; 330; layoff; educational investment; working students